Nonlinear spectral theory - Appell, Jürgen (De Gruyter series in nonlinear analysis and applications ;, 2004)
In view of the eminent importance of spectral theory of linear operators in many fields of mathematics and physics, it is not surprising that various attempts have been made to define and study spectra also for nonlinear operators. This book provides a co.